PROJECT-BASED LEARNING MODEL ASSISTED BY WORKSHEET: IT’S EFFECT ON STUDENTS’ CREATIVITY AND LEARNING OUTCOMES - Suwarno, S.; Wahidin, W.; Nur, Sofyan Hasanudin (JPBI (Jurnal Pendidikan Biologi Indonesia), 2020)
The low factor of learning outcomes is triggering by the emergence of students' boredom in learning. This study aimed to determine the effect of Project-Based Learning (PjBL) Models assisted by the Science Worksheet on Applied Waste Management on students' creativity and learning outcomes. This research was a quasi-experimental study. The population was all students in Vocational High School 1 Cikedung, Indonesia, and the sample was 57 students from two classes. Learning outcomes data obtained through tests with multiple-choice questions while creativity data using response questionnaires. The data obtained were analyzed using a one-way analysis of covariance. The results showed there was a significant effect of the learning model on students' creativity and learning outcomes. It concluded that the PBL model assisted in the worksheet has a positive impact on student competencies, especially on their creativity and biology learning outcomes.